Bronchial Thermoplasty in Patients with Severe Persistent Asthma: A Literature Review. Issue 4 (4th July 2021) - Aftab, Ghulam Mustafa; Rehman, Sana; Ahmad, Mudassar; Akram, Ali; Bukhari, Amar
ABSTRACT: The literature review aimed to see the safety and efficacy of bronchial thermoplasty in patients with severe asthma. We searched the online database, PUBMED, using bronchial thermoplasty and asthma as the key words and including trials from 2007 to 2021. Our review found that bronchial thermoplasty reduces asthma-related hospitalizations, emergency room visits and asthma exacerbations with sustained benefits for 5–10 years. This came at the expense of increased asthma-related adverse events, most commonly during the 7 days immediately after the procedure. Adverse events from 6 weeks after procedure to up to 5 years were similar between the bronchial thermoplasty group and the medication-only group. Bronchial thermoplasty is a safe and efficacious treatment modality for patients with severe asthma.